Synergistic effect of Li–Ti and K–Ti co-doping on the dehydrogenation properties of NaAlH4: an ab initio study. Issue 92 (20th September 2016) - Yu, Suye; Li, Shina; Wan, Chubin; Ju, Xin
Abstract : The synergistic effect of Li–Ti and K–Ti dopants on the energy, structure and electronic properties of NaAlH4 has been investigated using DFT and AIMD. Abstract : The synergistic effect of Li–Ti and K–Ti dopants on the energy, structure and electronic properties of NaAlH4 has been investigated using density functional theory and ab initio molecular dynamics. Pair distribution functional analyses show that the substitution of NaAlH4 by Li2 Ti and K2 Ti favor not only the release of H2 but also the reductions in the barrier energies of (AlH4 ) − units. Density of states analyses suggest that the weakening of Al–H bonds in Li2 Ti- and K2 Ti-doped NaAlH4 is attributed to the formation of Ti–Al and Ti–H phases. Bader atomic charges analyses imply that the strong interaction of Li–Al prevent the further formation of Ti–Al clusters. The results of H removal energies analyses reveal that both Li2 Ti and K2 Ti are favorable catalysts for NaAlH4 . Thus, that a Li2 Ti dopant, with lighter weight than K2 Ti, can be applied as a favorable catalyst for NaAlH4 has been given for the first time.